EFL Teachers’ Beliefs in Learner Autonomy: A Study on Non-Formal Education Context in Indonesia - Jannatul Ma'wa; Suwarsih Madya (Indonesian Journal of EFL and Linguistics, 2021)
This descriptive quantitative study aims to describe teachers’ beliefs in learner autonomy (LA) with participants who are senior high school teachers of non-formal education (Paket C) in Indonesia. Applying a survey method, this research involved 126 teachers fill a questionnaire. The research uncovers that teachers were knowledgeable about the notion of LA. Teachers were convinced that LA contributes to successful language learning. This research also uncovered that among four perspectives (psychological, technical, sociocultural, political critical) in viewing LA, teachers’ beliefs lean more toward psychological perspective than others. Although teachers were knowledgeable about LA, the research found that they were less optimistic in the implementation of LA. In addition to this, teachers’ beliefs in LA were not significantly different across their education backgrounds and length of teaching.